The challenges of safety improvement in New Zealand public hospitals. (2nd January 2019) - Beaver, Peter
ABSTRACT: Patient Safety is central to the New Zealand (NZ) health strategy. However international experience shows that safety improvement work frequently fails to meet its objectives. This article provides a qualitative account of the challenges of safety improvement from the perspective of nurses, doctors, and managers in three departments in two NZ public hospitals. These staff described significant tensions in relation to engagement and organisational capacity. An analysis of their perspectives through the Organising for Quality model [Bate et al. 2008, Organising for quality: The improvement journeys of leading hospitals in Europe and the United States, Oxford & New York, Radcliffe Publishing] highlights the significance of failures at the level of structure, culture, politics, motivation and infrastructure.